Late Effects of Organ Preservation Treatment on Swallowing and Voice; Presentation, Assessment, and Screening - Patterson, J. M. (Frontiers in Oncology, 2019)
The prevalence of head and neck cancer survivors is on the rise. Treatments for head and neck cancer can have a major deleterious impact on functions such as swallowing and voice. Poor functional outcomes are strongly correlated with distress, low quality of life, difficulties returning to work and socializing. Furthermore, dysphagia can have serious medical consequences such as malnutrition, dehydration and pneumonia. A conservative estimate of the percentage of survivors living with dysphagia in the long-term is between 50-60%. Evidence is emerging that functions can worsen over time, sometimes several years following treatment due to radiation-associated fibrosis, neuropathy, intractable oedema and atrophy. Muscles lose their strength, pliability, stamina, and range, speed, precision and initiation of movements necessary for swallowing and voice functions. Late treatment effects can go unrecognised, and may only be identified when there is a medical complication such as hospitalization for aspiration pneumonia. In the routine healthcare setting methods of evaluation include a detailed case history, a thorough clinical examination and instrumental assessments. Interventions for late treatment effects are limited and it is imperative that patients at risk are identified as early as possible. This paper considers the role of screening tests in monitoring swallowing and detecting aspiration in the long-term. Further work is indicated for addressing this pressing and increasingly common clinical problem.